Constitutional Implementation of Affirmative Action Policies in India - Sönmez, Tayfun; Yenmez, M. Bumin (The Review of Economics and Statistics, 2024)
Abstract India is home to a comprehensive affirmative action program that reserves a fraction of positions at governmental institutions for various disadvantaged groups. While there is a Supreme Court-endorsed mechanism to implement these reservation policies when all positions are identical, courts have refrained from endorsing explicit mechanisms when positions are heterogeneous. This lacuna has resulted in widespread adoption of unconstitutional mechanisms, countless lawsuits, and inconsistent court rulings. By formulating mandates from the landmark Supreme Court judgment Saurav Yadav vs The State of U.P. (2020) as technical axioms, we show that the 2SMH-DA mechanism is uniquely suited to overcome these challenges.